Perancangan dan Analisis Daya Turbin Air Piko Hidro untuk Aliran Arus Rendah - Nia Nuraeni Suryaman; Raden Herdian Bayu Ash Siddiq; Neris Peri Ardiansyah (Politeknik Negeri Padang, 2023)
Over time, the consumption of electrical energy needed in Indonesia is getting bigger. Various efforts continue to be made either by seeking new energy potential or by developing existing technologies. Apart from the increasing need for electrical energy, efforts are made to supply the needs of electrical energy by utilizing the potential and conditions that exist in certain areas. Water energy has been widely utilized and used for power generation. The potential of water as an energy source can be used as a provider of electrical power. One of the uses of water energy is to make hydroelectric power plants. The purpose of this study is to design a portable water turbine design and find out the results of the calculation of the analysis of electrical power produced. The research method used is the analysis of water turbine design using the SolidWorks application to be able to find out the shape of the turbine that has simple, portable properties and can be carried anywhere. The size that meets the desired criteria is 10 cm for diameter and 4 cm for height. After designing the turbine design, then the calculation and analysis of the power released by the water turbine is carried out. The data needed to perform the calculation are water discharge 1.48×10-5 m3/s, head 6×10-2 m, water density 1000 kg/m3, gravity acceleration 9.81 m/s2, turbine efficiency 12.6%. Using the turbine power formula, the turbine power with a water discharge value of 1.48×10-5 m3/s is 11 Watts. Then the 2nd calculation was carried out with the value of the water discharge used of 9.6×10-5 m3/s and turbine efficiency of 24.9%. After calculation, the turbine power value of 14 Watts was obtained.